2014
DOI: 10.1038/ncomms6201
|View full text |Cite
|
Sign up to set email alerts
|

Chlamydia infection depends on a functional MDM2-p53 axis

Abstract: Chlamydia, a major human bacterial pathogen, assumes effective strategies to protect infected cells against death-inducing stimuli, thereby ensuring completion of its developmental cycle. Paired with its capacity to cause extensive host DNA damage, this poses a potential risk of malignant transformation, consistent with circumstantial epidemiological evidence. Here we reveal a dramatic depletion of p53, a tumor suppressor deregulated in many cancers, during Chlamydia infection. Using biochemical approaches and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
66
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(72 citation statements)
references
References 60 publications
(72 reference statements)
5
66
0
1
Order By: Relevance
“…Cml blocked both bacterial replication and inclusion expansion ( Fig. 2A-C), suggesting that protein synthesis is required for chlamydial inclusion expansion, corroborating a recent observation (Gonzalez et al, 2014). Together, these data suggest that the C. trachomatis inclusion can expand in the absence of bacterial replication.…”
Section: Inclusion Expansion Is Dependent On Protein Synthesis But Nosupporting
confidence: 85%
“…Cml blocked both bacterial replication and inclusion expansion ( Fig. 2A-C), suggesting that protein synthesis is required for chlamydial inclusion expansion, corroborating a recent observation (Gonzalez et al, 2014). Together, these data suggest that the C. trachomatis inclusion can expand in the absence of bacterial replication.…”
Section: Inclusion Expansion Is Dependent On Protein Synthesis But Nosupporting
confidence: 85%
“…They demonstrated that sustained p53 downregulation is the key event that prevents apoptosis in Chlamydia-infected cells and that this is actively mediated by Chlamydia via the p53-MDM2 axis and ubiquitination (76,77). These important in vitro findings demonstrate that it is not just via innate immune and pathogen defense pathways that Chlamydia impacts the cell, but other central host cell pathways are also fundamentally required for the pathogen's survival.…”
Section: Immune Pathway Elucidated By In Vitro Culture Modelsmentioning
confidence: 84%
“…Recently, two teams demonstrated important links among apoptosis, cell survival, and carcinogenesis for Chlamydia (76,77). They demonstrated that sustained p53 downregulation is the key event that prevents apoptosis in Chlamydia-infected cells and that this is actively mediated by Chlamydia via the p53-MDM2 axis and ubiquitination (76,77).…”
Section: Immune Pathway Elucidated By In Vitro Culture Modelsmentioning
confidence: 99%
“…Eradication of p53 was shown to depend on PI3K/AKT signaling and HDM2-mediated p53 ubiquitination and proteasomal degradation. Gonzalez et al showed that p53 depletion is, at least to some extent, important for chlamydial apoptosis resistance (Gonzalez et al 2014). Moreover, Siegl and co-workers described an additional role of p53 during Chlamydia infection related to the host cell metabolism.…”
Section: Depletion Of P53mentioning
confidence: 97%
“…Dependent on the degree of damage, p53 also induces apoptosis by the stimulation of Bax and Bak oligomerization as well as increased gene expression of multiple pro-apoptotic proteins such as Bax, Puma, or Noxa (Siegl and Rudel 2015). Chlamydia actively deplete p53 levels during infection and enriched p53 levels in the cell interfere with chlamydial inclusion formation and replication (Siegl et al 2014;Gonzalez et al 2014). Eradication of p53 was shown to depend on PI3K/AKT signaling and HDM2-mediated p53 ubiquitination and proteasomal degradation.…”
Section: Depletion Of P53mentioning
confidence: 97%